Eats more, shoots & leaves : why, ALL punctuation marks matter! - Truss, Lynne (G.P. Putnam's Sons, 2019)
Simple sentences and illustrations show the importance of punctuation by using the same wording but changing the punctuation to highlight what a change the right markings can make.